Evaluating Effectiveness, Relevance, and Endurance in a Solar-Powered DC Hands-On Activity Using Rasch Modeling - Ngia Masta; Kisei Manai; Manogari Sianturi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Renewable Energy based Hands-on experimental kits are essential for enhancing student engagement and conceptual understanding in physics education. This study evaluates the feasibility of a Solar-Powered Direct Current (SP-DC) experimental kit, focusing on its effectiveness, relevance, and endurance as perceived by users. A quantitative design was employed using a closed-ended questionnaire comprising 14 items. Participants (n=79) consisted of undergraduate students from Universitas Kristen Indonesia (n=36) and high school students from SMA N 11 Jakarta (n=43). Prior to completing the questionnaire, students engaged in assembling the SP-DC kit and measuring current and voltage. Data were collected between June 2022 and June 2023 and analyzed using the Rasch model through Winstep version 5.9.00. Fit validity was determined by item and person statistics (MNSQ, ZSTD, PTMEA), while descriptive analysis included item measures and score distributions. Findings confirmed that all questionnaire items met Rasch model validity criteria, with PTMEA correlations above 0.7. In terms of effectiveness, participants reported favorable perceptions of ease of use and assembly, though aspects such as portability and storage required improvement. Relevance was demonstrated through the kit’s role in supporting understanding of series and parallel circuits, motivating interest in renewable energy, and strengthening connections between theory and practice. Endurance analysis revealed that the kit was generally durable and safe, though operational robustness could be enhanced. The SP-DC experimental kit is a feasible educational tool that supports effectiveness, curricular relevance, and endurance. These results suggest the kit’s potential for broader application in both secondary and higher education.